x^2n+(2x)^n+4^(n-1) 因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 02:38:15
x^2n+(2x)^n+4^(n-1)因式分解x^2n+(2x)^n+4^(n-1)因式分解x^2n+(2x)^n+4^(n-1)因式分解x^2n+(2x)^n+4^(n-1)=(x^n)^2+2*2
x^2n+(2x)^n+4^(n-1) 因式分解
x^2n+(2x)^n+4^(n-1) 因式分解
x^2n+(2x)^n+4^(n-1) 因式分解
x^2n+(2x)^n+4^(n-1)
=(x^n)^2+2*2^(n-1)*x^n+[2^(n-1)]^2
=[x^n+2^(n-1)]^2
=(xn- 1_22n)2
x^2n+(2x)^n+4^(n-1)
=(x^n)^2+2^nx^n+2^2(n-1)
=(x^n)^2+2*2^(n-1)x^n+[2^(n-1)]^2
=[x^n+2^(n-1)]^2
f(x)=e^x-x 求证(1/n)^n+(2/n)^n+...+(n/n)^n
因式分解:x^(2n)+(2x)^(n)+4^(n-1)
x^2n+(2x)^n+4^(n-1) 因式分解
若(x^2+1/x)^n(n∈N+,n
x^(n)*x^(n+1)+x^(2n)*x
(4x^n-2x^n-1-3x^n+2)÷(-5x^n-1)
因式分解4x^(n+2)-9x^n+6x^(n-1)-x^(n-2)
因式分解4x^n+2-9x^n+6x^n-1-x^n-2
x^n-1(3x^n+4x^n+1-5x^n+2)
因式分解:(x^n+1)+(2x^n)+(x^n-1)
x^n+1-2x^n+x^n-1因式分解
x^n-1-2x^n+x^n-1因式分解
(x^4n/x^2n)*x^n
分解因式x^n-x^(n-1)+x^(n-2)
x^n-2x^n+1,因式分解
4x^n+2-9x^n+6x^n-1-x^n-24x^(n+2)-9x^n+6x^(n-1)-x^(n-2),n是整数且大于2
x^n*x^n+1*(-x)^2n*x+(-x)^2n+3x^2n-2*x
(8x^n+1-3x^n-1)-2(-x+9x^n+1-4x^n)=